Using Real Options to Help Build the Business Case for CRM Investment - Maklan, Stan; Knox, Simon; Ryals, Lynette (Elsevier Science B.V., Amsterdam., 2005)
The long-term benefits of implementing a Customer Relationship Management programme are widely accepted as being: learning from customers, building customer retention, and reduced market uncertainty. Yet high rates of failure in CRM can originate right at the stage where the investment decisions are made. Traditional discounted cashflow analysis alone does not value or focus managerial attention upon the strategic long-term benefits of CRM. Through a simulated case study analysis, this paper illustrates how the addition of Real Options to discounted cashflow can improve CRM investment decision making, encourage managers to verify critical assumptions and reduce both investment and business risk.